2022
DOI: 10.1016/j.ridd.2022.104178
|View full text |Cite
|
Sign up to set email alerts
|

Short Report: The influence of congregate setting on positive COVID-19 tests among a high-risk sample of adults with intellectual and developmental disability in Ontario

Abstract: Background For a number of reasons, persons with intellectual and developmental disability (IDD) are at increased risk of contracting COVID-19. Aims This study explored the influence of congregate setting on testing positive for COVID-19 among adults with IDD in Ontario. Methods and procedures 833 home care recipients with IDD were included, 204 were tested at least once for COVID-19. These data were linked to the homecare assessment data. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Only nine studies (16%) focussed, at least in part, on Autistic adults with intellectual disability [ 13 •, 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. For the 35 studies (64%) including Autistic adults’ self-report data, it is likely that participating adults did not have a co-occurring intellectual disability, since self-report requires the ability to understand and respond to questions (orally or in writing), usually without support.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only nine studies (16%) focussed, at least in part, on Autistic adults with intellectual disability [ 13 •, 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. For the 35 studies (64%) including Autistic adults’ self-report data, it is likely that participating adults did not have a co-occurring intellectual disability, since self-report requires the ability to understand and respond to questions (orally or in writing), usually without support.…”
Section: Resultsmentioning
confidence: 99%
“…through the use of proxy-reports or medical records), the highest proportion of Autistic females was 39% [ 22 ] (excluding one study, where the single Autistic participant was female [ 25 ]). In 12 of 55 studies (22%), Autistic adults’ gender/sex was not reported, mostly because either professionals were the primary informant [ 28 , 29 , 30 ] or the sex ratio was described only for a larger group of participants with an intellectual or developmental disability (IDD) [ 18 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, those who tested positive for COVID-19 were not eligible, in order to focus on those experiencing precautions without a COVID-19 diagnosis. An earlier study identified that older age was associated with testing positive for COVID-19 [8] . It is possible that most of the older home care clients residing in congregate settings tested positive for COVID-19 and thus not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported an increased risk of COVID-19 diagnosis and mortality among those with IDD [ 7 , 8 , [14] , [15] , [16] ], and IDD status was one of the most significant predictors of COVID-19 mortality in the United States [7] . Increased age (OR=1.04 per year; 95% CI, 1.02-1.06), Down syndrome (OR=2.91; 95% CI, 1.49-5.69), chronic kidney disease (OR=4.17; 95% CI, 1.90-9.15) [14] , living in a congregate setting (OR=3.01; 95% CI 1.49-6.09) [8] , and living in settings with a higher number of residents (OR=1.07; 95% CI, 1.0-1.14) [14] have been associated with COVID-19 diagnosis among adults with IDD. Heart disease (OR=6.59, 95% CI 4.51, 9.62) and Down syndrome (OR=10.60, 95% CI, 2.68-41.90) were also risk factors for COVID-19 mortality [14] .…”
Section: Introductionmentioning
confidence: 99%
“…People with ID have an increased risk of COVID-19 diagnosis, morbidity, and mortality ( 9 , 10 ). The risk factors of COVID-19 morbidity and mortality among people with ID include increased age, living in a congregate setting, chronic kidney disease, heart disease and Down syndrome ( 11 , 12 ). People with ID face isolation and precaution-related challenges, including emotional and behavioral disturbance from restricting usual activities and social isolation ( 8 , 13 ).…”
Section: Introductionmentioning
confidence: 99%